The End of British Politics? - Moran, Michael. author. aut Link
XII, 104 p.
Keywords: 'Michael Moran has pulled off that most difficult of feats. In the midst of a crisis he has written a classic which will stand the test of time. His synthetic account of the development of the British state bears comparison with Ralf Dahrendorf’s classic Society and Democracy in Germany (1969). Building on the work of Bulpitt, Dyson and others, Moran presents a compelling account of the British state. Full of very powerful insights, it has a limpid clarity and freshness that has no rivals in recent books on British politics.' – Professor William Paterson OBE, University of Aston, UK This book explores the crisis of the British state. Though it has been particularly apparent since the outcome of both the 2014 Scottish independence and 2016 ‘Brexit’ referendums, it stems from deep historical roots. The book traces the origins of the state to the original Act of Union of 1707 and demonstrates how different notions of Britishdestiny - Protestant, imperial, social democratic – have held the state together at different times. The present crisis, it is argued, is due to the exhaustion of these senses of destiny. Moran shows how the United Kingdom is now held together as a militarised state prone to disastrous adventures like the invasion of Iraq, and concludes by examining some alternative futures for the state. This book will appeal to students, scholars and the general reader interested in British politics and political history. Michael Moran is Emeritus Professor of Government at the University of Manchester and Professor of Government in the Alliance Business School, University of Manchester, UK. Among his publications are the textbook Politics and Governance in the UK and the monograph The British Regulatory State.